(untitled) (Research, Society and Development, 2022)
Cardiac surgeries are serious procedures that, although considered safe, are accompanied by complex processes. In this context, respiratory physiotherapy is an integral part of cardiac patient care management, both preoperatively and postoperatively, as it significantly contributes to a better prognosis. in the case of a patient who is going to or has already undergone CABG surgery, physiotherapy becomes important, as it contributes to a better patient’s recovery. Objective was to describe the effects of physical therapy on the rehabilitation of patients before and after myocardial revascularization surgery. This is a systematic search through the search for articles in the SciELO, PubMed/MEDLINE and BIREME databases. One hundred and four (104) articles were found in the searched databases; of these, nine (9) were included to compose the discussion. Studies have shown that respiratory physiotherapy techniques are very important and that, through aerobic physical activities, it contributes to avoid complications in recovery, reduces pain and improves quality of life, also showing effectiveness in other cardiovascular events. As a final consideration, the study showed that preoperative physical therapy proved to be a tool that can help physical therapists in the rehabilitation of patients, facilitating their recovery and that it should be a practice adapted to the characteristics of the population served.